2014
DOI: 10.5935/abc.20140088
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and Vascular Endothelium

Abstract: Involvement of the cardiovascular system in patients with infectious and parasitic diseases can result from both intrinsic mechanisms of the disease and drug intervention. Malaria is an example, considering that the endothelial injury by Plasmodium-infected erythrocytes can cause circulatory disorders. This is a literature review aimed at discussing the relationship between malaria and endothelial impairment, especially its effects on the cardiovascular system. We discuss the implications of endothelial aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…9 This may allow the accumulation of infected erythrocytes in the myocardial capillaries, leading to mechanical obstruction, reduced tissue perfusion, and disease. 13,14 Although less common, studies have also demonstrated how P. vivax-infected erythrocytes also may adhere to the endothelium. 11,13,78 Likely, accumulation in the capillaries and microcirculation in the myocardium may result in regional dysfunction, leading to pathological alterations in ECG, biomarkers, and echocardiographic parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 This may allow the accumulation of infected erythrocytes in the myocardial capillaries, leading to mechanical obstruction, reduced tissue perfusion, and disease. 13,14 Although less common, studies have also demonstrated how P. vivax-infected erythrocytes also may adhere to the endothelium. 11,13,78 Likely, accumulation in the capillaries and microcirculation in the myocardium may result in regional dysfunction, leading to pathological alterations in ECG, biomarkers, and echocardiographic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Although less common, studies have also demonstrated how P. vivax-infected erythrocytes also may adhere to the endothelium. 11,13,78 Likely, accumulation in the capillaries and microcirculation in the myocardium may result in regional dysfunction, leading to pathological alterations in ECG, biomarkers, and echocardiographic parameters. Those are the same parameters that we found affected in a majority of clinical studies of P. falciparum patients on admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…falciparum malaria [ 2 , 4 6 ]. After malaria infection, the endothelial cells can be activated by different mechanisms such as the binding of soluble cytokines, mediated by pro-inflammatory cytokines present in host serum [ 7 , 8 ], direct contact with infected RBCs, and activation induced by parasite-derived molecules such as hemozoin and glycosylphosphatidylinositol (GPI). These factors can induce endothelial injury and apoptosis which lead to increase in vascular permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Colomba et al reported similar findings in a malaria case and suggested that local inflammation might increase vascular permeability, leading to accumulation of pericardial fluid [ 6 ]. Other suggested mechanisms include cytoadhesion of infected erythrocytes to the coronary endothelium [ 17 ] and release of pro-inflammatory cytokines due to vascular endothelial dysfunction in the myocardial vessels [ 18 , 19 ]. Despite a plethora of proposed mechanisms, no consensus exists as to how malaria affects the heart.…”
Section: Discussionmentioning
confidence: 99%